Democracy and responsiveness in maritime country: Interrelations between 'blusukan' of jokowi and the development of insfrastructure of ocean toll - Ladiqi, S.; Salleh, M.A. (2018)
In the context of the Asian financial crisis of 1997, a dictatorship in Indonesia that had lasted more than 30 years finally came to an end. Indonesia's transition process featured, among other aspects, a general overhaul and liberalization of the political system, including the establishment of a multiparty system, freedom of the press and the first free and fair elections in the country since 1956. The important thing is capturing relations between the state and the people as change phenomenon from authoritarianism toward transition democracy. Putting the people as a pivotal aspect of the context state relations is crucial democracy discussion not only reflected by people participation but also government responsiveness through pro poor policy or welfare policy. It should be discussing democracy in a complete definition. Implementation of democracy should reflection not only of people such as participation and representativeness measure but also for the people such as responsiveness measure.Understanding the relationship between the state and the people in the context of responsiveness through infrastructure development will certainly be more interesting when the 'Blusukan' method is put into the frame of development program implementation. Implementation of democracy such as "for the people" is evident in the government's efforts to meet the needs of the people (responsive) through pro people policy making In addition to the existing institutional supervision, with the Blusukan method, Jokowi wants to get accurate, fast and direct get information from the people. This activity not only wants to bring the state closer to the people but also at the same time wants to control the implementation of infrastructure development that is and will be run.